Abdominal Aortic Diameter and the Risk for Asymptomatic Peripheral Arterial Disease in Patients with Type 2 Diabetes - Amer, Moatasem Salah; Omar, Omar Hussien; Reda, Randa Abdel Wahab; Rahman, Tomader Taha Abdel; Rasheedy, Doha (International Journal of Angiology, 2015)
Peripheral arterial disease (PAD) is common among older people because it often results from atherosclerosis, which becomes more common with age. The disease is particularly common among people who have diabetes. Little information is available on the relation between abdominal aortic diameter and PAD in elderly patients with diabetes. This article studies the relationships between abdominal aortic diameter, PAD, and the cardiovascular risk factors in asymptomatic elderly patients suffering from type 2 diabetes mellitus. A case–control study was conducted on 90 participants aged 60 years and older divided into 60 cases (30 males and 30 females) and 30 age-matched healthy controls (15 males and 15 females). The relationships between the size of the abdominal aorta and ankle–brachial index (ABI), plasma cholesterol, triglycerides (TG), and high-sensitivity C-reactive protein were examined. Approximately, 15% of patients with diabetes had asymptomatic PAD. The patients with diabetes with PAD were of older age (70.4 ± 3.6 vs. 63.4 ± 3.9 years; p = 0.000), had larger abdominal aortic diameter (22.4 ± 3.08 vs. 18.7 ± 2 mm; p = 0.000), and higher CRP levels (8.3 ± 1.1 vs. 5.8 ± 2.2 mg/L; p = 0.002), while other variables revealed no significant difference. Abdominal aortic diameter correlated well with ABI measured by Doppler method in diabetic patients (r =  − 0.471, p = 0.000). Older age and larger abdominal aorta are independent risk factors for asymptomatic PAD in the elderly with type 2 diabetes mellitus.
Keywords: peripheral arterial disease; abdominal aortic diameter; diabetes mellitus; ankle–brachial index; C-reactive protein